Numerical investigation of aerodynamic characteristics of high speed train - Syed Mohamed Ali, Jaffar; Omar, Ashraf Ali; Ali, Muhammad Atif; Mohd Baseair, Abdul Rahman (Institute of Physics (IOP) Publishing, 2017)
In this work, initially the effect of nose shape on the drag characteristics of a high speed train is studied. Then the influence of cross winds on the aerodynamics and hence the stability of such modern high speed trains is analyzed. CFD analysis was conducted using STAR-CCM+ on trains with different features and important aerodynamic coefficients such as the drag, side force and rolling moment coefficients have been calculated for yaw angles of crosswinds ranging from 0° to 90°. The results show that the modification on train nose shape can reduce the drag up to more than 50%. It was also found that, bogie faring only reduces small percentage of drag but significantly contributed to higher rolling moment and side force coefficient hence induced train instability.